Features of translation transformations in film titles as a linguoculturological specificity of the language - Kaneeva Anna; Bagdasaryan Tatyana (E3S Web of Conferences, 2021)
The article offers a classification of translation techniques based on the analysis of Russian-language titles of foreign films. The choice of film titles as the research material is due to the greatest complexity of their translation in comparison with other texts. this opens up wide opportunities for studying translation transformations as a reflection of the linguistic and cultural specifics of the language. In the name of any film, linguistic and cultural features are understandable only to a native speaker play an important role. However, some must necessarily be translated into another language, while preserving the originality, attractiveness and capacity. All this forces the interpreter to search for and use translation transformations more actively than when working with other texts. The article deals with various types of transformations associated with the need for linguistic and cultural reinterpretation of the text in the cultural space of the recipient country. The use of linguistic and cultural studies allows us to more fully and accurately convey to the consciousness of perceiver the semantic content of the film, starting with its name, taking into account the inclusion of the translation in the cultural archetypes and codes of the native language.